The Understanding of Covenant in The Book of Jeremiah: An Exegetical Study of Jeremiah 11:2-5 - Gosal, Fellix (Klabat Theological Review, 2025)
This study examines the theological, historical, and literary aspects of the covenant concept found in Jeremiah 11:2–5. Using the Mosaic Covenant as the backdrop for Jeremiah 11, the study highlights the covenant's provisions for benefits for obedience and punishments for disobedience, as well as its relationship to the book of Deuteronomy. The passage emphasizes how Judah's idolatry and disobedience caused the covenant to break down, resulting in unavoidable divine judgment. The study employs an exegetical methodology to examine the text's delimitation, literary structure, historical context, and theological implications. The results show that the covenant in Jeremiah 11 is a divine order based on an oath rather than just an agreement, and that disobedience will result in curses like calamity and unanswered prayers. The fact that God is still the covenant's creator and guarantor in spite of human failure emphasizes His power to renew it. According to the study's findings, the covenant establishes and preserves the bond between God and His people, with disobedience resulting in punishment and obedience bringing prosperity. Keywords: Covenant, Jeremiah 11, Mosaic Covenant, Exegesis, Blessings and Curses, Divine Punishment, Oath, Idolatry, Disobedience, Theological Implications.